Kritik Sosial Terhadap Adat Minangkabau Dalam Novel Tenggelamnya Kapal Van Der Wijck - Resti Ramadhani; Resti Izwar; Syakila Risti Aura; Abdurahman . (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study examines the social criticism of Minangkabau customs in the novel Tenggelamnya Kapal Van der Wijck by Hamka. The novel not only presents a tragic love story between Zainuddin and Hayati but also conveys profound criticism of the social system and traditional customs within Minangkabau society, particularly regarding social stratification, matrilineal lineage, and perceptions of social status. The purpose of this research is to identify the forms of social criticism expressed by the author and analyze their relevance to societal conditions.This research employs a qualitative approach using content analysis techniques. The data were collected through an in-depth reading of the novel and analyzed using the perspective of sociology of literature. The findings reveal that Hamka strongly criticizes rigid and discriminatory customary practices, especially in matchmaking processes that prioritize social status over love and personal character. Furthermore, the novel highlights the marginalization of individuals who are not considered to have “pure” Minangkabau lineage, as experienced by the character Zainuddin, who faces social rejection. In conclusion, the novel serves as a medium of social criticism toward traditional practices that are no longer aligned with human values and justice.